Analisis Popularitas Laman Pemerintah Daerah Di Wilayah Malang Raya Berbasis Perangkat Pemeringkatan Dalam Jaringan - Dian Wahyuningsih, Sujito , (SMATIKA, 2015)
This study aims to reveal the popularity of pages governments in Malang by using two devices in the network ratings are www.alexa.com and checkpegerank.net. Alexa ranking basis is the number of visits (traffic) to a particular survived, while checkpagerank.net based on the number of links to a particular page. Third wesbite Malang local government has not implemented fully Instruksi Presiden No 3 Tahun 2003 on the development of national policies and strategies of e-goverenment because there is not yet public service that is easy and inexpensive. Given public service is merely the procedure to get the service but have not been able to accommodate the public service through the pages. Malangkota.go.id page has the highest ratings by alexa.com, while batukota.go.id page has the highest ratings by checkpagerank.net. Local governments need to add advertising and social media links in order to boost ratings so as to attract people to visit it.